Universal versus conditional three-day follow up visit for children with uncomplicated fever at the community level: design of a cluster-randomized, community-based, non-inferiority trial in Tanganyika, Democratic Republic of Congo. Issue 1 (December 2017) - van Boetzelaer, Elburg; Ho, Lara; Gutman, Julie; Steinhardt, Laura; Wittcoff, Alison; Barbera, Yolanda; Ngoy, Pascal; Harvey, Steven; Mullany, Luke
Abstract Background The current recommendation within integrated Community Case Management guidelines that all children presenting with uncomplicated fever and no danger signs be followed up after three days may not be necessary. Such fevers often resolve rapidly (usually within 48–96 h), and previous studies suggest that expectant home care for uncomplicated fever can be safely recommended. We aim to determine the non-inferiority of a conditional versus a universal follow-up visit for these children. Methods We are conducting a cluster-randomized, community-based, non-inferiority trial enrolling 4300 children (ages 2–59 months) presenting to community health workers (CHWs) with uncomplicated fever in Tanganyika Province, Democratic Republic of the Congo. Clusters (n = 28) of CHWs are randomized to advise caretakers of such children to either 1) return for a follow-up visit on Day 3 following the initial consultation (Day 1), regardless of illness resolution (as per current guidelines) or 2) return for a follow-up visit on Day 3 only if the child's signs have not resolved. Enrolled children are followed up at Day 7 for a repeat assessment and recording of the primary outcome of the study, "failure", which is defined as having fever, diarrhea, pneumonia or decline of health status (e.g. hospitalization, presenting danger signs, or death). Discussion The results of this trial will be interpreted in conjunction with a similarly designed trial currently ongoing in Ethiopia. If a follow-up visit conditional on continued illness is shown to be non-inferior to current guidelines stipulating universal follow-up, appropriate updating of such guidelines could reduce time and human resource pressures on both providers and caregivers throughout communities of sub-Saharan Africa and South Asia. Trial registration This trial was registered at ClinicalTrials.gov (NCT02595827 ) on November 2nd, 2015